Globalization And Digital Transformation As Demographic And Green Economic Policies In Southeast Asia - Hamka, Hamka (Institute Of Advanced Knowledge and Science, 2025)
Developing countries in Southeast Asia are still relatively young compared to other regions around the world. However, recent statistics suggest that the situation is beginning to change in this regard, with many of these populations aging at a much faster rate than in many other countries. These developments require urgent policy action to create a sustainable path to economic growth before demographic changes become less benign in the medium term. discusses the economic consequences of population aging, rising economic support ratios, and declining potential growth rates. It is critical for developing countries in Southeast Asia to increase their total productivity (TFP) growth rates to achieve more sustainable economic outcomes. By conducting panel regressions using data from 82 countries over the study period 1996–2019, our study shows that increasing research and development (R&D) spending and facilitating structural changes that transform the digital economy landscape are key policy options that boost TFP growth. Globalization has significantly affected the economy, ecology, and society over the past decade. Meanwhile, the green economy has emerged as an important policy framework for growth and development in both developed and developing countries. The current study is an attempt to provide a detailed overview of globalization, green economy, and climate challenges to draw some implications. There is disagreement between competing green economy discourses and various definitions, all of which have problems. Recognizing the environmental impacts of natural resource depletion and the economic benefits of environmental management are common examples of operationalizations of the green economy. The new study also examines the impact of climate change on the green economy and infrastructure development.